Research status and development trend of ultrasonic oil production technique in China - Wang, Zhenjun; Xu, Yuanming; Suman, Bajracharya (Ultrasonics sonochemistry, 2015)
This paper presents an overview of research status and development trend of ultrasonic oil production technique for Enhanced Oil Recovery in China. As one of EOR techniques, ultrasonic oil production attracts more attention due to its simplicity, lower expenses, good applicability and no reservoir pollution. Through the comparison of the development of ultrasonic oil production both in China and other countries, this paper summarize the recent research progress in ultrasonic oil production techniques and practices in China. Finally, the development of oil production equipment and development trend of ultrasonic oil production technique in China are given.